Construction of a food-grade arginase expression system and its application in L-ornithine production with whole cell biocatalyst. (October 2018) - Kai, Huang; Xiao, Guan; Bo, Jiang; Sen, Li
Graphical abstract: Highlights: A food grade recombinant Bacillus subtilis was constructed for arginase production. Antibiotic resistance selection marker was replaced by a dal gene in the plasmid. Deletion of argF was to eliminate the effect of ornithine carbamoyltransferase. High production was obtained with a fed-batch strategy. Efficient whole cell biocatalyst has great potential for L-ornithine production. Abstract: A food-grade recombinant Bacillus subtilis overexpressing arginase from Rummeliibacillus pycnus was successfully constructed based on replicative plasmids. D-Alanine racemase gene on the host chromosome was knocked out with Cre/ lox system. Replacement of antibiotic resistance gene with dal in the plasmids would complement the deletion of the host strain and offer a selective pressure to keep plasmid segregational stability. Further deletion of argF was carried out to eliminate any effect of ornithine carbamoyltransferase. Then, constructed plasmid was transformed into engineered B. subtilis for arginase expression. The highest arginase activity in fermentation broth reached 42.1 U/mL at 16 h, and harvested cells could be used directly in L-ornithine bioconversion. Whole cell bioconversion was optimized and the reaction conditions were as follows: 200 g/L L-arginine, 1.5 mM Mn 2+, pH 9.5 and 45 °C. In a scale up study, a final L-ornithine concentration of 342.2 g/L was obtained with a fed-batch strategy. The molar yield was calculated to be 90.2% with only 9.8 g/L L-arginine residue. Performance showed that this highly efficient whole cell biocatalyst has great potential for industrial L-ornithine production.